THE DOWNSIDE OF CYBERSPACE: CHEATING MADE EASY. - Gibelman, Margaret; Gelman, Sheldon R.; Fast, Jonathan (Journal of Social Work Education)
This article explores the actual and potential misuses of the World Wide Web in regard to access to "paper mills" and other information sources that make plagiarism relatively easy. The authors describe their experience accessing such paper mill products and present results of a quasi-experiment in which participants graded three papers: one an actual student submission and two purchased off the internet. Findings suggest reason for concern about student misuse o( the World Wide Web. The authors argue that different strategies for the design of class assignments must be considered by all educational programs to diminish enhanced opportunities for "cybercheating."